2021
DOI: 10.3389/fnmol.2021.771103
|View full text |Cite
|
Sign up to set email alerts
|

Promoter Hypomethylation of miR-124 Gene Is Associated With Major Depressive Disorder

Abstract: Based on our previous studies and other evidence, miR-124 is an important biomarker and therapeutic target for major depressive disorder (MDD). The aim of this study was to clarify the role of miR-124 methylation in MDD and antidepressant effects from the perspective of epigenetics. MethylTarget™ was used to detect methylation levels of the three miR-124 precursor genes (MIR124-1, MIR124-2, and MIR124-3) in 33 pre- and post-treatment MDD patients and 33 healthy controls. A total of 11 cytosine-phosphate-guanin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Our previous research also supported metabolomics has potential in biomarkers exploration related to the diagnosis and treatment of mental disorders 47 48. In addition, emerging fields, known as epigenomics and microbiome, have shown some degree of association with prognosis 49–52…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…Our previous research also supported metabolomics has potential in biomarkers exploration related to the diagnosis and treatment of mental disorders 47 48. In addition, emerging fields, known as epigenomics and microbiome, have shown some degree of association with prognosis 49–52…”
Section: Introductionsupporting
confidence: 62%
“…47 48 In addition, emerging fields, known as epigenomics and microbiome, have shown some degree of association with prognosis. [49][50][51][52] Current studies of gut microbiota-brain axis and neuroimmunology suggest a need for integrated analysis. Decreased faecal microbiota richness and diversity were observed in some MDD studies and associated with altered serum metabolites and decreased immunoglobulin.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…In the past few years, a considerable amount of research has been conducted to examine the role of miRNAs in neuropsychiatric disease [147][148][149][150][151][152][153][154][155][156]. We and other investigators have examined the expression of miRNAs in human postmortem brains of depressed subjects, in the brain of animals showing depression-like behavior, and in peripheral tissues such as blood, urine, and saliva [6,96,144,150,[157][158][159][160][161][162][163][164][165][166][167]. We have demonstrated that miRNAs form highly correlated networks in the brains of MDD subjects that differ from healthy controls, suggesting that miRNA networks can give rise to specific behavioral phenotypes [96,168,169].…”
Section: Studies Of Dna Methylation In Adolescents With Elsmentioning
confidence: 99%
“…Our findings of the involvement of miR-124 in regulating the FTO gene via transcription factor C/EBP-α are highly relevant. We and other investigators have shown that miR-124-3p plays a crucial role in synaptic plasticity and stress-related disorders ( Sun et al, 2015 ; Dwivedi, 2017 ; Roy et al, 2017a ; Gu et al, 2019 ; Yang et al, 2020 ; Zeng et al, 2021 ). Knockdown of miR-124 reduces depression-like behavior in chronic unpredictable stress–induced depressive rats ( Yang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 82%